Day 2 Wed, March 27, 2019 2019
DOI: 10.2523/iptc-19240-ms
|View full text |Cite
|
Sign up to set email alerts
|

Extended Acoustic Sand Monitoring Helps to Understand Ceramic Sand Screen Failure: A Case Study

Abstract: Many oil and gas fields have long been suffering from sand production due to either the absence or failure of primary well sand control. To avoid mobilizing costly work-over rig to pull out the tubing, operators have tried various thru-tubing remedial sand control. The well's condition such as sands accumulation and space constraints due to small inner diameter of tubing always make this remedial job challenging. It is not surprising that the results are not all satisfactory. Among the industry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…According to Riyanto et al [ 12 ], the major challenge associated with SAS is screen erosion and methods are being introduced to improve screens which led to the development of Ceramic Sand Screens, and the use of alloys and exotic materials (shape memory screens, expandable sand screens ESS, etc.) to improve the surface structure for resisting erosion.…”
Section: Stand-alone Screen Types Selection Criteria and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to Riyanto et al [ 12 ], the major challenge associated with SAS is screen erosion and methods are being introduced to improve screens which led to the development of Ceramic Sand Screens, and the use of alloys and exotic materials (shape memory screens, expandable sand screens ESS, etc.) to improve the surface structure for resisting erosion.…”
Section: Stand-alone Screen Types Selection Criteria and Performancementioning
confidence: 99%
“…Many authors have examined causes and failure modes of SAS. Most of these studies concluded that screen erosion is by far the most common failure mechanism [ [58] , [59] , [60] ]. Screen erosion is due to the mechanical wear of the retention media, weave or wire.…”
Section: Sand Screen Integrity and Failurementioning
confidence: 99%